Consequences multi-channel sales – customers and retailers perspective - Lipowski, M. (Видавництво Львівської політехніки, 2014)
Проаналізовано, як мережева економіка, інформаційні та комунікаційні технології модифікують поведінку та переваги споживачів. Багато виробників продають свої товари в роздрібних магазинах, через каталоги, електронну пошту, соціальні мережі, телефон, онлайн-магазини, мобільні додатки, а також через ринкових посередників. Досліджено ефект мультиканальних продажів з погляду як покупця, так і продавця. Мультиканальні продажі дають можливість клієнту самостійно вирішувати, як, коли і де купувати товари та замовляти послуги. Запропоновано розглядати кожен канал збуту не окремо, а в сукупності з іншими для забезпечення ефекту синергії. Проаналізовано взаємний вплив каналів та переваги мультиканальних продажів як для продавців, так і для покупців. Network economy, ICT technology modify consumer behaviour and purchase habits. Many providers sells their offer today in the physical retail stores, through catalogues, e-mail, social networking sites, by phone, online store, mobile applications as well as market intermediaries. The aim of the article is to present the effects of multichannel sales. Both from the point of view of the consumer and the manufacturer/seller. Multichannel selling gives customer opportunity to chose how, when and where to buy goods and services. The researcher suggest to treat every distribution channel not as a separate system but manage them in order to find synergy. Different channel influence each other. Multichannel selling bring retailers: higher selling, higher lifetime value of consumer, higher cost managing multi-channel selling, better information about customers, more competitive market. Multichannel give customer: convenience, less cost/effort, flexibility buying, lower level of service. In the online environment and the network economy gradually blurs differences between communication and distribution channel.
Наслідки мультиканальних продажів та перспепктиви для клієнтів та продавців
Keywords: мультиканальний розподіл; маркетинговий канал; поведінка споживачів; multi-channel distribution; marketing channels; customer behaviour